(untitled) (Mugda Medical College Journal, 2025)
A cross-sectional, descriptive study was conducted in the selected rural areas of Nawabganj upazila under Dhaka district, Bangladesh, between January and December of 2017, to see the association of dysmenorrhoea with menstrual pattern and body mass index (BMI) of adolescent girls. Adolescents who were unmarried, attained menarche at least 2 years before study period and willing to participate were included in the study. However, adolescents who were suffering from diseases like ovarian cyst, endometriosis, pelvic inflammatory disease, and/or taking hormonal pills were excluded from the study. Based on inclusion and exclusion criteria, a total of 312 girls (between 13 and 19 years) were finally selected for the study. Data collection was done using a semi-structured questionnaire, which included participants age, height, weight, menstrual history, clinical features of dysmenorrhoea and medication history. Data was collected through face-to-face interview. Dysmenorrhoea was assessed using the ‘verbal multidimensional scoring system’. Body Mass Index (BMI) was determined as weight divided by height squared (kg/m2). The mean age of the participants was 15.7±1.23 years. 70.5% of the total participants reported some forms of dysmenorrhoea: 25.3% experienced mild dysmenorrhoea, while 23.1% had moderate and 22.1% had severe dysmenorrhoea. Regarding menstrual patterns, no association was observed with dysmenorrhoea (p>0.05); however, the relationship of positive family history and prevalence of dysmenorrhoea was statistically significant (p<0.05). No association was observed between body mass index (BMI) and dysmenorrhoea among female adolescents (p>0.05). Mugda Med Coll J. 2025; 8(2): 96-100